Jaguar density in the Argentine Yungas: overcoming camera trap failure - Reppucci, JI; Perovic, PG; Cuyckens, GAE; Caruso, F; de Bustos, S; Arrabal, JP; Sillero-Zubiri, C (Elsevier, 2023)
The Yungas ecoregion supports an important jaguar population, of particular conservation relevance due to its location in the extreme SW of the species distribution, with potential for range extension and population recovery. Detailed population estimates are lacking. To evaluate jaguar density in the Argentine Yungas we conducted a camera trap survey in Baritú National Park and surrounding private lands. We deployed 32 sampling stations with a pair of camera traps each, obtaining a sampling effort of 2,080 trap/nights. Camera malfunction translated in several individual jaguars’ photo-captured only from one side, thus preventing unequivocal identification to apply traditional spatially explicit capture-recapture models. We used 2-flank SPIM, a partial identity spatially explicit capture-recapture model, we estimated a density of 0.75 jaguars per 100 km2, with a probability of detecting one side and both sides of 0.01 and 0.02 respectively. Our density estimates are low, but within the range of other studies, especially those on the fringes of the species distribution and support the idea of Yungas offering a stronghold for Argentina’s jaguars. This study offers a baseline for a monitoring program, much needed in a priority jaguar population.